Bibliometric analysis of media reporting of suicide: A worldview - Sujita Kumar Kar; Kritika Chawla; Babli Kumari; Ankita Saroj; Amit Singh; Bandna Gupta; Adarsh Tripathi; Shashwat Saxena (Indian Journal of Health Sciences and Biomedical Research KLEU, 2022)
Suicide is a global mental health challenge and suicides frequently get a wide media coverage. The media reporting of suicide and subsequent suicides are closely associated. Studies reveal country wise variations in the quality of media reporting. We aimed to do a bibliometric analysis of the published research on media reporting of suicide. All the published articles available on the PubMed database from the time of inception till August 2021 were included in the study. All the PubMed IDs of the articles were entered in Harvard Catalyst, a free online software, for bibliometric analysis, and data were extracted and verified. A total of 158 published articles were identified. The average number of authors per article was 5.108 and the average number of times an article cited was 9.639 (excluding self-citation). The h-index of the published articles was 19. The Crisis journal published the maximum number of articles (n = 24). The highest number of average citations was for systematic reviews. Maximum articles were published in 2020 (n = 27). Suicide reporting in the media is an important subject of suicide research. However, original studies on this subject are few. Large-scale studies will contribute to the development of an evidence base for future recommendations and guidelines on this important subject.